Proceedings of the 2014 International Conference on Quantitative InfraRed Thermography 2014
DOI: 10.21611/qirt.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

Coupling infrared thermography and acoustic emission for damage study in CFRP composites

Abstract: Improvement of the design and reliability of aeronautical composite structures requires an identification and characterization of their damage evolution. By providing surface thermal fields, infrared thermography has allowed considerable progress in the detection of degradation phenomena. On the other hand, acoustic emission is employed to record the transient waves resulting from released energy during a damage process. This study intends to combine simultaneously these nondestructive methods to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…There are other valuable studies wherein damage accumulation in carbon fiber-reinforced laminates have been reported using structural health monitoring techniques such as Infrared thermography (IRT), Digital image correlation (DIC), and Acoustic emission (AE). 1821…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other valuable studies wherein damage accumulation in carbon fiber-reinforced laminates have been reported using structural health monitoring techniques such as Infrared thermography (IRT), Digital image correlation (DIC), and Acoustic emission (AE). 1821…”
Section: Introductionmentioning
confidence: 99%
“…There are other valuable studies wherein damage accumulation in carbon fiber-reinforced laminates have been reported using structural health monitoring techniques such as Infrared thermography (IRT), Digital image correlation (DIC), and Acoustic emission (AE). [18][19][20][21] The size effect is a crucial parameter that greatly impacts the overall strength of the structure and affects the structural integrity and damage accumulation. An increment in the laminate thickness by the addition of further lamina increases the overall thickness and volume of the structure, which signifies that the area under stress has been increased.…”
Section: Introductionmentioning
confidence: 99%